Water conservation benefits of urban heat mitigation. Issue 1 (December 2017) - Vahmani, Pouya; Jones, Andrew
Abstract Many cities globally are seeking strategies to counter the consequences of both a hotter and drier climate. While urban heat mitigation strategies have been shown to have beneficial effects on health, energy consumption, and greenhouse gas emissions, their implications for water conservation have not been widely examined. Here we use a suite of satellite-supported regional climate simulations in California to show that broad implementation of cool roofs, a heat mitigation strategy, not only results in significant cooling, but can also meaningfully decrease outdoor water consumption by reducing evaporative and irrigation water demands. Irrigation water consumption across the major metropolitan areas is reduced by up to 9% and irrigation water savings per capita range from 1.8 to 15.4 gallons per day across 18 counties examined. Total water savings are found to be the highest in Los Angeles county, reaching about 83 million gallons per day. Cool roofs are a valuable solution for addressing the adaptation and mitigation challenges faced by multiple sectors in California. Cool roofs have been shown to mitigate heat in urban areas, but their impact on water conservation has not been examined. Here the authors conduct simulations with an urban canopy model to show that implementation of cool roofs in California can also reduce outdoor water consumption by up to 9%.